PENGARUH KECERDASAN EMOSIONAL, KOMPETENSI, BUDAYA KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR OTORITAS PELABUHAN UTAMA BELAWAN - Hetti Mariati Simangunsong; Parulian Siregar; Basrun Siagian; Fatimatu Risna; Habibah Saragih (Universitas Islam Islam Sumatera Utara, 2021)
Problem of this study what is influence of emotional intellegence on performance. What is influence of competency on performance. What is influence of job culture on performance. What is influence of job satisfaction on performance. What is influence emotional intellegence, competency, job culture and job satisfaction on performance. The purpose of this study to determine and analyze the effect of emotional intellegence on performance. Determine and analyze the effect of competency on performance. Determine and analyze the effect of job culture on performance. Determine and analyze the effect of job satisfaction on performance. Determine and analyze the effect of emotional intellegence, competency, job culture and job satisfaction on performance. Sample in the study is 74 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate emotional intellegence has a positive and significant effect on performance. competency has a positive and significant effect on performance. Job culture has a positive and significant effect on performance. Job satisfaction has a positive and significant effect on performance. Emotional intellegence, competency, job culture and job satisfaction has a positive and significant effect on performance.